Epigenetic analysis of patients with T-ALL identifies poor outcomes and a hypomethylating agent-responsive subgroup - Touzart, Aurore; Mayakonda Thippeswamy, Anand; Smith, Charlotte; Hey, Joschka; Toth, Reka; Cieslak, Agata; Andrieu, Guillaume P.; Quang, Christine Tran; Latiri, Mehdi; Ghysdael, Jacques; Spicuglia, Salvatore; Dombret, Hervé; et al. (Science translational medicine, 2021)
Targeting adult T-ALL epigenetics - “T cell” acute lymphoblastic leukemia (T-ALL) is an aggressive blood cancer with poor survival that has been understudied in adults. Here, Touzart et al. studied the epigenetics of adult T-ALL and identified five subgroups based on the amount of methylation present in the genome. Two of these subgroups were associated with more aggressive disease: a hypomethylated subgroup and, unexpectedly, a substantially hypermethylated subgroup. The authors then showed that 5-azacytidine, a hypomethylating agent, delayed tumor progression in mice with hypermethylated cancers. Although further study is needed, the findings suggest that hypomethylating agents could be an alternative or an adjunct to existing therapies for patients with hypermethylated T-ALL. - Adult "T cell" acute lymphoblastic leukemia (T-ALL) is an aggressive hematological malignancy that is associated with poor outcomes, requiring additional therapeutic options. The DNA methylation landscapes of adult T-ALL remain undercharacterized. Here, we systematically analyzed the DNA methylation profiles of normal thymic-sorted T cell subpopulations and 143 primary adult T-ALLs as part of the French GRAALL 2003-2005 trial. Our results indicated that T-ALL is epigenetically heterogeneous consisting of five subtypes (C1-C5), which were either associated with co-occurring DNA methyltransferase 3 alpha (DNMT3A)/isocitrate dehydrogenase [NADP(+)] 2 (IDH2) mutations (C1), TAL bHLH transcription factor 1, erythroid differentiation factor (TAL1) deregulation (C2), T cell leukemia homeobox 3 (TLX3) (C3), TLX1/in cis-homeobox A9 (HOXA9) (C4), or in trans-HOXA9 overexpression (C5). Integrative analysis of DNA methylation and gene expression identified potential cluster-specific oncogenes and tumor suppressor genes. In addition to an aggressive hypomethylated subgroup (C1), our data identified an unexpected subset of hypermethylated T-ALL (C5) associated with poor outcome and primary therapeutic response. Using mouse xenografts, we demonstrated that hypermethylated T-ALL samples exhibited therapeutic responses to the DNA hypomethylating agent 5-azacytidine, which significantly (survival probability; P = 0.001 for C3, 0.01 for C4, and 0.0253 for C5) delayed tumor progression. These findings suggest that epigenetic-based therapies may provide an alternative treatment option in hypermethylated T-ALL. - Characterization of adult T-ALL methylomes identifies a clinically aggressive hypermethylated subgroup sensitive to 5-azacytidine. - Characterization of adult T-ALL methylomes identifies a clinically aggressive hypermethylated subgroup sensitive to 5-azacytidine.
Gesehen am 26.08.2021